If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + -3x = 11 + -8x Solving 85 + -3x = 11 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 85 + -3x + 8x = 11 + -8x + 8x Combine like terms: -3x + 8x = 5x 85 + 5x = 11 + -8x + 8x Combine like terms: -8x + 8x = 0 85 + 5x = 11 + 0 85 + 5x = 11 Add '-85' to each side of the equation. 85 + -85 + 5x = 11 + -85 Combine like terms: 85 + -85 = 0 0 + 5x = 11 + -85 5x = 11 + -85 Combine like terms: 11 + -85 = -74 5x = -74 Divide each side by '5'. x = -14.8 Simplifying x = -14.8
| 1+1+x= | | 12+x^2=8x-12 | | x-3=0.5*x | | -2x^2-1=-2x | | 4a^2-1=0 | | 17y+14X-183W= | | 4w+3x-y+4w-14x-6y= | | 5x-3y+14w-4y-6w-6x= | | 3K-4=3 | | 8(2X+1)=-16 | | 5M-4=49 | | 7x*28=77 | | 6=x-2 | | (x-8)(2x+9)=0 | | 4w+8y+5x+6x-15y+4w= | | 58-7x=2x+17 | | 12-7x=2x+17 | | m^2-8m+12=0 | | 4w+6x+13y+4w+5x-6y= | | 3M-3=10 | | 98-2x=6x+10 | | 3x^5y^3+15x^3y^2+15xy= | | 59-2x=25x+20 | | (y-9)-(y+3)=8y | | 14-9x=90-23x | | 0=3x+-1x^2 | | 5x-8=-6x+4 | | 14a+20b+3c+2c-5b-6a= | | 66-10x=7x+19 | | 2b-10b+12=0 | | x^2-3x+c=0 | | 3(4x^2-6x+9)=0 |